Penerapan Metode Praktikum untuk Meningkatkan Kinerja dalam Mata Pelajaran IPAS Materi Perubahan Wujud Zat Kelas Iv - Ega Rizky Ardiansyah; Ibnu Muthi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The use of practical methods in teaching material on changes in the states of matter is very effective in helping students understand these concepts in more depth. Through practicum, students can directly observe how a substance changes form under certain conditions, such as temperature or pressure, this strengthens theoretical understanding with practical experience. Using practical methods in teaching changes in the states of matter, students not only understand theoretical concepts but also see their application in real life. This can help build a more holistic and in-depth understanding of the material studied. The practicum method encourages students to be more active and participate in the learning process. Class observations showed that 85% of students were more engaged and enthusiastic during practicum sessions compared to conventional learning. They often ask questions, discuss and try to understand the material through direct experiments. Students are trained to make careful and systematic observations of changes in the state of substances. The evaluation results show an increase in these skills by 25% after implementing the practicum method. The application of practicum methods in learning science and material regarding changes in the states of substances in class IV has proven to be effective in improving various aspects of learning. This method succeeded in increasing conceptual understanding, science process skills, student activity and participation, academic performance, and learning motivation. Students involved in practicum activities showed a significant increase in understanding the concept of changes in the states of matter, as shown by an increase in the average score of 30%.